2013
DOI: 10.1152/jn.00115.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to theta-burst timing permits LTP in dorsal striatal adult brain slice

Abstract: Long-term potentiation (LTP) of excitatory afferents to the dorsal striatum likely occurs with learning to encode new skills and habits, yet corticostriatal LTP is challenging to evoke reliably in brain slice under physiological conditions. Here we test the hypothesis that stimulating striatal afferents with theta-burst timing, similar to recently reported in vivo temporal patterns corresponding to learning, evokes LTP. Recording from adult mouse brain slice extracellularly in 1 mM Mg 2ϩ , we find LTP in dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 90 publications
3
57
0
Order By: Relevance
“…Consistent with the facilitating role of the amygdala in associative memory3435 and cortico-striatal plasticity28, frequencies in the theta range, alone or when combined with higher-frequencies, have been shown to promote long-term potentiation of cortico-striatal3637, including prefronto-striatal30, synaptic efficacy. Such plasticity may rely in the temporal relationship of striatal spikes to the ongoing theta rhythm as found in hippocampal place cells38.…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with the facilitating role of the amygdala in associative memory3435 and cortico-striatal plasticity28, frequencies in the theta range, alone or when combined with higher-frequencies, have been shown to promote long-term potentiation of cortico-striatal3637, including prefronto-striatal30, synaptic efficacy. Such plasticity may rely in the temporal relationship of striatal spikes to the ongoing theta rhythm as found in hippocampal place cells38.…”
Section: Discussionmentioning
confidence: 77%
“…Stimulation of cortical afferents with the TBS reliably induces NMDAR-dependent LTP at these synapses in normal Mg 2+ solution (Hawes et al, 2013). Consistently, we also found that LTP could be induced from most (7/8) of recorded MSNs by TBS with the same total number of stimuli as that of HFS used above (Figure 1E; see Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…Pairing presynaptic stimulation with postsynaptic depolarization (Pawlak and Kerr, 2008; Shen et al, 2008) was also effective in NMDAR- and D1/D5R–dependent LTP at corticostriatal synapses, but the same pairing stimulation could also result in LTD induction (Shindou et al, 2011). On the other hand, TBS could reliably induce LTP that requires the activation of both NMDARs and BDNF signaling at both corticostriatal synapses (Figure 1G and 3B; Hawes et al, 2013) and hippocampal synapses (McGuinness et al, 2010; Zakharenko et al, 2003; Zakharenko et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…To ensure our studies were physiologically relevant, spike-timing dependant plasticity paradigms were used (Pawlak and Kerr, 2008) that most likely mimic in vivo stimulation patterns observed during striatal based learning (DeCoteau et al, 2007a,b; Tort et al, 2008; Hawes et al, 2013). Methods employed to generate slices preserved thalamic and cortical inputs onto striatal output neurons, and also retained output basal ganglia nuclei, thus retaining striatal inputs and outputs as well as feedback loops (Beurrier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%